Windows into the Visual Brain: New Discoveries about the Visual System, Its Functions, and Implications for Practitioners. (July 2013) - Jan, James E.; Heaven, Roberta K. B.; Matsuba, Carey; Langley, M. Beth; Roman-Lantzy, Christine; Anthony, Tanni L.
Introduction: In recent years, major progress has been made in understanding the human visual system because of new investigative techniques. These developments often contradict older concepts about visual function. Methods: A detailed literature search and interprofessional discussions. Results: Recent innovative neurological tests are described that are able to show much more accurately the visual pathways, the process of vision, and the close relationships among sensory modalities. These tests also reveal the remarkable neuroplasticity of the human brain and disorders of connectivity that frequently involve visual function. Discussion: How these recent neurological advances may benefit service providers is discussed. Implications for practitioners: It is important that from time to time new neurological and ophthalmic developments are summarized for professionals who are involved in the clinical management of individuals with visual disorders and how the newly acquired knowledge affects the diagnosis and intervention strategies. Visual rehabilitation must be based on up-to-date science, which continually changes and grows with research.